Characterization of Bacteriophages Infecting Clinical Isolates of Clostridium difficile - Phothichaisri, Wichuda; Ounjai, Puey; Phetruen, Tanaporn; Janvilisri, Tavan; Khunrae, Pongsak; Singhakaew, Sombat; Wangroongsarb, Piyada; Chankhamhaengdecha, Surang (Frontiers in Microbiology, 2018)
Clostridium difficile is recognized as a problematic pathogen, causing severe enteric diseases including antibiotic-associated diarrhea and pseudomembranous colitis. The emergence of antibiotic resistant C. difficile has driven a search for alternative anti-infection modalities. A promising strategy for controlling bacterial infection includes the use of bacteriophages and their gene products. Currently, knowledge of phages active against C. difficile is still relatively limited by the fact that the isolation of phages for this organism is a technically demanding method since bacterial host themselves are difficult to culture. To isolate and characterize phages specific to C. difficile, a genotoxic agent, mitomycin C, was used to induce temperate phages from 12 clinical isolates of C. difficile. Five temperate phages consisting of ɸHR24, ɸHN10, ɸHN16-1, ɸHN16-2, and ɸHN50 were successfully induced and isolated. Spotting assays were performed against a panel of 92 C. difficile isolates to screen for susceptible bacterial hosts. The results revealed that all the C. difficile phages obtained in this work displayed a relatively narrow host range of 0 to 6.5% of the tested isolates. Electron microscopic characterization revealed that all isolated phages contained an icosahedral head connected to a long contractile tail, suggesting that they belonged to the Myoviridae family. Restriction enzyme analysis indicated that these phages possess unique double-stranded DNA genome. Further electron microscopic characterization revealed that the ɸHN10 absorbed to the bacterial surface via attachment to cell wall, potentially interacting with S-layer protein. Bacteriophages isolated from this study could lead to development of novel therapeutic agents and detection strategies for C. difficile.